2015
DOI: 10.1007/s10067-015-3146-0
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic measures of settlement phenomenon in patients with medial compartment knee osteoarthritis

Abstract: In this study, we proposed for the first time the theory of "settlement phenomenon" in tibial plateau and carefully explored the role of settlement of tibial plateau in the occurrence and progression of medial compartment knee osteoarthritis (OA) through investigating the relationship between the degree of settlement and the radiographic severity of OA. One hundred twenty-seven patients with knee medial compartment OA were recruited and examined with weight-bearing radiographs of the entire lower limb. The rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 23 publications
3
68
2
1
Order By: Relevance
“…suggested that malalignment of the lower limbs, such as varus deformity, would lead to a gradual increase in the load of the medial compartment of the knee joint, which would greatly escalate the risk of the progression of knee osteoarthritis. The theory of “non‐uniform settlement” suggested that osteoporosis around the knee joint and the supporting effect of fibula lead to non‐uniform settlement of the knee joint, the medial tibial plateau collapsed under long‐term compressive stresses, which lead to alignment varus, more overloads on the medial compartment, degeneration of articular cartilage, and final knee varus and osteoarthritis. It showed that deformation was one of the pathogenic factors of KOA.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…suggested that malalignment of the lower limbs, such as varus deformity, would lead to a gradual increase in the load of the medial compartment of the knee joint, which would greatly escalate the risk of the progression of knee osteoarthritis. The theory of “non‐uniform settlement” suggested that osteoporosis around the knee joint and the supporting effect of fibula lead to non‐uniform settlement of the knee joint, the medial tibial plateau collapsed under long‐term compressive stresses, which lead to alignment varus, more overloads on the medial compartment, degeneration of articular cartilage, and final knee varus and osteoarthritis. It showed that deformation was one of the pathogenic factors of KOA.…”
Section: Introductionsupporting
confidence: 81%
“…Knee varus is the morphological manifestation of medial compartment KOA. The phenomenon of “non‐uniform settlement” suggested that knee varus started at medial tibial plateau collapsed as long‐term pressure overload led to alignment varus, more overloads on the medial compartment, and degeneration of articular cartilage. Age was an important risk factor for KOA as it increased the length of weightbearing over time.…”
Section: Discussionmentioning
confidence: 99%
“…Risk of compartment‐specific progression in the analysis of medial OARSI grade progression increased in the presence of bipolar “kissing” defects, and risk of lateral OARSI grade progression increased in the presence of tibial defects. The higher rates of medial compared to lateral compartment progression are consistent with a higher prevalence of medial compartment OA seen in the general population …”
Section: Discussionsupporting
confidence: 64%
“…According to the World Health Organization criteria (1994), the interpretation of the T score is as follows: T score >−1: normal, T score between −1 and −2.5: osteopenia, and T score <−2.5: osteoporosis. Hip X-ray examination was performed to diagnose the radiological signs of OA (Ravaud et al 1999). The Harris Hip Score (HHS) was also calculated in OA patients (Nilsdotter and Bremander 2011).…”
Section: Patients Populationmentioning
confidence: 99%